2011
DOI: 10.2139/ssrn.1852365
|View full text |Cite
|
Sign up to set email alerts
|

More Bits – More Bucks? Measuring the Impact of Broadband Internet on Firm Performance

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
(4 reference statements)
1
13
0
3
Order By: Relevance
“…A few studies use data on sub-national variation in the availability of internet infrastructure as an instrument for internet usage at the firm-level to estimate its impact on firm productivity. Bertschek et al (2013) and Haller and Lyons (2015) find an insignificant impact of broadband internet on firm productivity in Germany and Ireland, respectively, whereas Grimes et al (2012) and Akerman et al (2015) find a positive impact of broadband internet on firm productivity in New Zealand and Norway, respectively. The latter study 6 They draw on the exogenous features of the historic subterraneous fiber-optic and copper-wire telephone network which is the infrastructure through which broadband internet is delivered in the United Kingdom.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…A few studies use data on sub-national variation in the availability of internet infrastructure as an instrument for internet usage at the firm-level to estimate its impact on firm productivity. Bertschek et al (2013) and Haller and Lyons (2015) find an insignificant impact of broadband internet on firm productivity in Germany and Ireland, respectively, whereas Grimes et al (2012) and Akerman et al (2015) find a positive impact of broadband internet on firm productivity in New Zealand and Norway, respectively. The latter study 6 They draw on the exogenous features of the historic subterraneous fiber-optic and copper-wire telephone network which is the infrastructure through which broadband internet is delivered in the United Kingdom.…”
Section: Literature Reviewmentioning
confidence: 98%
“…For example, inBertschek et al (2013) the estimating sample of firms in Germany starts in the early 2000s when 60 percent of firms already had access to broadband internet in Germany. 9 For instance, term life insurances are a standardized product that has seen significant declines from online price comparisons, but more differentiated whole-life insurances are less amenable to online price comparisons and have therefore not seen a comparable decline in prices(Brown and Goolsbee, 2002).…”
mentioning
confidence: 99%
“…Overall, our results suggest that IT investment by itself does not trigger enhanced productivity, but is part of a broader productivity‐enhancing suite of innovations. Other empirical studies have come to similar conclusions (Bertschek et al ., ; Colombo et al ., ). For example, Haller and Lyons () found that while more productive firms were more likely to adopt broadband, there was no evidence of causation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly a New Zealand study found that broadband adoption increased productivity by 7–10 per cent across a range of firms (Grimes et al ., ). However, a study of German businesses found that faster broadband had no significant impact on labour productivity in the two years covered by the study (though there was considerable variability among firms), but was linked to increased innovation (Bertschek et al ., ). This is suggestive that broadband, as with ICT more broadly, may be considered as a general purpose technology, resulting in reorganisation and innovation in the short term, with labour productivity gains more likely to occur later (Bertschek et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Diversas investigaciones han señalado que la inversión e implementación de las TI no incrementa la productividad automáticamente (Afflerbach, 2015;Brynjolfsson y Hitt, 2003). Este efecto ocurre principalmente por la falta de integración de las TI en la estructura organizacional, en donde se debe dar atención al nivel de capacitación de los empleados, gestión eficiente del conocimiento y mejora continua en las prácticas administrativas de las firmas (Alavi y Leidner, 2001;Bertschek et al, 2013;Sabherwal y Jeyaraj, 2015). Según Lichtenberg (1995), un empleado bien calificado, que trabaje con tecnologías de información, puede ser más eficiente que seis trabajadores que no conozcan cómo manejar y elaborar procesos con TI.…”
Section: Fig 1: Relación De La Gestión Del Conocimiento Con La Produunclassified